MOTIVASI BELAJAR BAHASA ARAB MELALUI AL-KUTUB AT-TURATS DI PONDOK PESANTREN MAMBA’US SHOLIHIN - Farid Qomaruddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2019)
Abstract: Moelem boarding school or pesantren is the oldest educational institution in Indonesia. Since its establishment, the pesantren has shown its role in broadcasting Islam and science which cannot be separated from the original language, namely Arabic. This can be seen from the historical journey of Muslims in Indonesia brought by the scholars. In this journey, pesantren had many contributions, because they were used as the basis for deepening the study of religious knowledge. The learning carried out in the pesantren covers many things, including through al-Kutub at-Turats, which is taught using Arabic through several methods, both traditional and contemporary methods. From this learning, it can be possible to provide motivation for students so that there is a relationship and synergy between learning al-Kutub at-Turats and learning Arabic. This article provides an overview of the motivation to learn Arabic through al-Kutub at-Turats which can be applied in Mamba'us Sholihin moeslem boarding school, explains the obstacles that may be faced in the implementation of learning motivation, and describes the efforts that can be made by pesantren in overcoming obstacles that will later exist in the application of motivation to learn Arabic for students through learning al-Kutub at-Turats .Keywords: Motivation, Moeslem Boarding School